RELATIONSHIP BETWEEN PSYCHOLOGICAL FATIGUE AND WORK STRESS WITH PERFORMANCE AMONG MOTHERS WORKING AT ALASA PUBLIC HEALTH CENTER, NORTH NIAS REGENCY - Taruli Rohana Sinaga; Rinawati Sembiring; Seri Asnawati Munthe; Mido Ester J Sitorus; Enjel Siska Dewita Hulu (Jurnal Ilmiah Keperawatan, 2026)
Working mothers in the health sector, particularly in community health centers, face the challenge of playing dual roles as professionals and homemakers. This situation has the potential to cause psychological fatigue and work stress, which can impact their performance. This study aims to analyze the relationship between psychological fatigue and work stress and their effects on the performance of working mothers at the Alasa Public Health Center (PHC) in North Nias Regency. This study is quantitative and cross-sectional. The sample comprised 36 married women employed at the Alasa PHC. Data were collected using a questionnaire that had been tested for validity and reliability. Data analysis was performed using univariate and bivariate analysis using the chi-square test. The results showed a significant relationship between psychological fatigue and performance (p = 0.0005 < α = 0.05) and a significant relationship between work stress and performance (p = 0.001 < α = 0.05). Mothers who experienced psychological fatigue and high work stress tended to show low performance. This situation is exacerbated by heavy workloads, significant domestic responsibilities, particularly within the family environment, lack of rest time, and minimal social support. This study recommends managerial efforts to identify and manage psychological factors affecting working mothers, including emotional support from superiors, colleagues, and family, adequate rest time, more flexible work schedules, and improved welfare. The implementation of these strategies is expected to reduce psychological fatigue and work stress, thereby significantly and measurably improving the performance of female health workers, particularly working mothers, thereby positively impacting overall performance.